6. Analisis Implementasi Cyber Security di Uni Eropa: Studi Kasus Carbon Credits Hacking dalam European Union Emission Trading Scheme (EU ETS) Tahun 2010-2013 - Aisya, Naila Sukma; Putranti, Ika Riswanti; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Since the last two decades in the 20th century, the European Union (EU) has presented itself as a leader in climate change issues. The leadership manifested in the formation of the European Union Emission Trading Scheme (EU ETS) as an effort to fulfill the commitments of the Kyoto Protocol to reduce emissions in the region. But the existence of the EU ETS has been challenged by the emergence of carbon credits hacking case in some national registration systems in the EU ETS. This study discusses the implementation of cyber security in the European Union which has not been able to prevent the occurrence of carbon credits hacking in 2010-2013. This study uses the collective identity and role identity concepts of constructivism. Collective identity explains the implementation of cyber security in the EU, while the role identity explains the effect of EU leadership on the issue of climate change. The results show that the collective identity of cyber security in the European Union has a systemic and strategic issue namely the lack of homogeneity of the implementation of the policies and the lack of perception of the cyber-attacks as a common threat. The EU itself tends to focus on achieving the emissions reduction commitments through the market mechanism in the EU ETS.